The Qur'an in South Asia: Hermeneutics, Qur'an Projects, and Imaginings of Islamic Tradition in British India - Bashir, Kamran (Routledge Studies in the Qur'an Ser., 2021)
Cover -- Half Title -- Series Information -- Title Page -- Copyright Page -- Dedication -- Note on Transliteration -- Table of Contents -- Preface -- Introduction -- Notes -- 1 Pre-Modern and Early Modern Qur'anic Hermeneutics in South Asia -- General Insights From the Historiography of South Asian Tafsīr -- Qur'anic Hermeneutics in Pre-Mutiny India -- Pre-Walī Allāh Hermeneutics -- Walī Allāh's Qur'anic Hermeneutics -- Post-Walī Allāh Hermeneutics -- Post-1857 Reception of Pre-Mutiny Qur'anic Thought -- Notes -- 2 The Qur'an and the Context of British India -- Europeans and the Qur'an -- Imagining the Prophet and Interpreting the Qur'an -- The Impact of Science and Historical Criticism -- The Rise of Print Technology in British India -- The Question of "Authentic" Islam in British India -- Institutionalized Knowledge Systems, the Muslim Mindset, and the Qur'an -- Arabic Literature and Delhi Literary Circles -- Empire, Networks of Ideas, and the Qur'an -- Notes -- 3 Introducing Muslim Qur'an Commentators and Commentaries in British India -- Notes -- 4 Sayyid Aḥmad Khān (1817-1898) -- Aḥmad Khān's Intellectual Formation and Works -- Aḥmad Khān's Principles of Qur'anic Interpretation -- Appreciating Aḥmad Khān's Art of Interpretation -- The Meaning of Malak in the Qur'an -- Aḥmad Khān's Linguistic Treatment of Other Qur'anic Vocabulary and Phrases -- Colonial India and Aḥmad Khān's Exegetical Ideas -- Intra-faith Rivalries -- Aḥmad Khān's View of Science -- Aḥmad Khān's Response to European Criticism of the Qur'an -- The Possibilities of Linguistic Analysis -- The Impact of Aḥmad Khān's Qur'an Project -- Notes -- 5 Ashraf ʿAlī Thānawī (1863-1943) -- Thānawī's Intellectual Formation and Works -- Thānawī's Works On the Qur'an -- Tafsīr Bayān Al-Qurʾān: Thānawī's Principles of Interpretation -- Thānawī's Interpretation of Sūrat Al-Baqara (Q 2).